PERTUMBUHAN MEGAURBAN KEDUNGSEPUR - Wilonoyudho, Saratri (Sekolah Pascasarjana UGM, 2011)
Over the last 20 years many urban areas have experienced dramatic growth, as a result of rapid population increase and the trans formation of the world economy because of a combination ofÂ rapid technological and political change. In the case of Kedungsepur, the area has seen more than twofold growth. Migrants come to the inner zones from both the areas core and elsewhere in the country. Net migration, in many case, contributes as much as two thirds of the population growth in these zones, whereas in the city cores, net migration contributes little to growth. A comprehensive model suggests that urbanization in Kedungsepur is influenced by structural and social demographic factors. Thus, the balance between managing urban discharges to the environment and enhancing environmental resource capacity is the key determinant of sustainability.